Effects of sustained silent reading on elementary students’ L1, L2, and L3 reading skills - Padilla, Portia P. (2021)
Accessed online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/8579
Keywords: Reading comprehension; Multilingualism in children; Education research